Cover Picture: A Study of Electrocyclic Reactions in a Molecular Junction: Mechanistic and Energetic Requirements for Switching in the Coulomb Blockade Regime (ChemPhysChem 12/2017). Issue 12 (12th June 2017) - Olsen, Stine T.; Brøndsted Nielsen, Mogens; Hansen, Thorsten; Ratner, Mark A.; Mikkelsen, Kurt V.
Abstract : The Front Cover picture illustrates the mechanistic and thermodynamic restrictions for dark photoswitching, which were theoretically elucidated for substituted for substituted oligoenes. More information can be found in the Full Paper by K. V. Mikkelsen and co‐workers onpage 1517 in Issue 12, 2017 (DOI:10.1002/cphc.201700140 ).